Tinjauan Ontologi Dan Epistemologi Dalam Game Edukasi Pada Siswa - Eko Subastian; Siti Masitoh; Mochamad Nursalim (JUPE : Jurnal Pendidikan Mandala, 2022)
Knowledge is essentially all that we know about a particular object including knowledge, attitudes, types of knowledge have specific characteristics about what (ontology) and how (epistemology). Therefore, the author makes an educational game based on the Android operating system in the hope that students can directly use the game application and gain more knowledge and change learning patterns so they don't get bored and bored. This educational game is a learning application for children aged 6 to 12 years which contains subject matter about animals, coloring, doodling, singing and the alphabet. The research and development method for this educational application is the Waterfall method which consists of five stages, namely Requirement, Design, Implementation, Verification, and Maintenance. By applying the results of this educational game, it is hoped that it can help children learn and can improve their creative mindset and add more advanced knowledge